THE IMPORTANCE OF TEACHING THE SUBJECT "LEGAL BASIS OF MEDICAL ACTIVITY" IN THE TRAINING OF FUTURE DOCTORS (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
The development of the socio-economic spheres of our republic, further improvement of the quality of personnel training in the system of higher and secondary specialized, higher education; increasing students' inquisitiveness, creativity, thinking abilities, and speech culture in vocational training based on modern achievements of science, technology, and technology; purposeful and effective use of information and communication technologies in mastering the secrets of professions; formation of students' skills for independent work is one of the most pressing problems of today.